High Prevalence of Rickettsia Slovaca in Dermacentor Marginatus in Euganean Hills Regional Park. (March 2022) - Grassi, L.; Drigo, M.; Cassini, R.; Mondin, A.; Pasotto, D.; Sinigaglia, R.; Rocca, G.; Menandro, M.L.
Abstract : Purpose: Rickettsia slovaca is a tick-borne zoonotic bacterium and is the etiological agent of SENLAT, Scalp Eschar and Neck Lymph-Adenopathy after Tick bite. Despite many human cases reported in Europe, its epidemiology is not completely understood. To further understand this neglected tick-borne pathogen, we collected ticks and wild boar blood samples in 2017 to evaluate R. slovaca prevalence. Due to the high prevalence detected in Dermacentor marginatus, we investigated archive tick and blood samples collected previously in 2010 monitoring activities. Methods & Materials: The research was conducted in Euganean Hills Regional Park, North-Eastern Italy. Sampling was performed in 2010 and 2017 and regarded both blood and ticks collected from wild boars at culling. In 2010, ticks were sampled from animals and from the vegetation using the dragging method. Ticks were identified using identification keys and processed for DNA extraction. Biological samples were screened by real-time PCR targeting Rickettsia gltA gene and positive samples were tested by classical PCR targeting gltA and ompB genes for species identification. Results: Overall, 89 wild boar blood samples were collected, 75 in 2010 and 14 in 2017. All samples tested negative. In addition, 254 tick samples were analysed, 233 sampled in 2010 and 21 in 2017. Four different tick species were identified: Dermacentor marginatus (n=190), Ixodes ricinus (n=58), Rhipicephalus sanguineus (n=5), and Hyalomma marginatum (n=1). A difference in R. slovaca prevalence was recorded among tick species, i.e, 23.68±6.05% in D. marginatus and 3.45±4.70% in I. ricinus while R. sanguineus and H. marginatum tested negative. In addition, ticks collected by dragging were negative, while a prevalence of 18.68%±5.66 and 61.90±20.77 was detected in ticks from wild boars sampled in 2010 and 2017, respectively. Conclusion: D. marginatus showed the highest prevalence of R. slovaca, revealing its important vectorial role. Comparing the tick sampling methods, dragging seems less informative than tick collection from wild boars. Since wild boars tested negative, their role in R. slovaca epidemiological cycle needs more investigations, while they act as a maintenance host of D. marginatus populations.